Deteriorative changes in oilseeds due to storage fungi and efficacy of botanicals - Ashok M. Chavan, Rajendra B. Kakde and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Improper storage makes the oilseeds vulnerable to storage fungi which deteriorate the stored oilseeds both qualitatively and quantitatively. They bring about the variety of biochemical changes in the suitable conditions. Considering this fact, experiments were undertaken to understand nutritional changes like change in reducing sugar, change in crude fat content and change in crude fiber content of oilseeds due to artificial infestation of storage fungi. It was found that, Alternaria dianthicola, Curvularia lunata, Fusarium oxysporum, Fusarium equiseti, Macrophomina phaseolina and Rhizopus stolonifer causes decrease in reducing sugar of oilseeds. Alternaria dianthicola, Curvularia pellescens, Macrophomina phaseolina, Penicillium digitatum and Penicillium chrysogenum hampered the fat content of oilseeds. Curvularia lunata, Curvularia pellescens, Fusarium oxysporum, Macrophomina phaseolina, Rhizopus stolonifer and Penicillium digitatum increased the fiber content in oilseeds. An attempt was also made to control the seed-borne fungi by using aqueous extract of ten medicinal plants. Aqueous extract of Eucalyptus angophoroides was found to be most fungitoxic.